A quick approach for medetomidine enantiomer determination in dog plasma by chiral liquid chromatography–tandem mass spectrometry and application to a pharmacokinetic study. Issue 7 (23rd February 2021) - Bardhi, Anisa; Zaghini, Anna; Levionnois, Olivier; Barbarossa, Andrea
Abstract: In the present study, a rapid, sensitive and high‐throughput liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for the determination of medetomidine enantiomers in dog plasma was developed and validated. The separation and individual quantification of chiral compounds can be a tricky task in LC. This is particularly true when target analytes have a relatively small mass, as is the case with medetomidine, a potent and highly specific α2‐adrenoceptor agonist widely used in both human and veterinary medicine. The proposed approach is based on a quick liquid–liquid extraction with ethyl acetate and filtration prior to injection. The optimized mobile phase composition allowed to perfectly separate the two enantiomers of medetomidine in a short chromatographic run time, using a cellulose tris(4‐methylbenzoate)‐based chiral column. A lower limit of quantification of 0.1 ng/mL was reached for both analytes thanks to the high sensitivity and selectivity of MS/MS and the use of racemic medetomidine‐d3 as internal standard prevented potential matrix effect. Linearity was satisfying ( R 2  > 0.99) over the range 0.1–25 ng/mL, as well as within‐ and between‐session accuracy and precision, both always <15%. This method was also applied with success to a series of samples from a pharmacokinetic (PK) study aimed at comparing dex‐ and levomedetomidine behaviour after administration of the racemic mixture in dogs. The simple extraction procedure, which allows reduced solvent and time consumption without compromising analytical performances, makes this technique a useful tool for this kind of applications even when small animals are involved, due to the small amount of sample required. Abstract : Thanks to chiral chromatography‐tandem mass spectrometry, medetomidine enantiomers can be individually and accurately quantified in plasma. This simple and eco‐friendly technique allows to quickly process large batches of samples with limited solvent consumption and requiring just a small aliquot of matrix. This makes it a very useful tool for pharmacokinetics studies and was successfully employed to compare the kinetics of dex‐ and levo‐medetomidine after administration of the racemic mixture in dogs.